Influence of Brand Image, Self-Congruence, and Brand Love on Brand Sacredness and Word-of-Mouth: Insights from Emina Skincare Users - Widiastuti, Dinda Rachma Amalia Nurtyas; Sekarsari, Larasati Ayu (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Purpose: This study examines the effects of brand image, self-congruence, and brand love on brand sacredness and word-of-mouth (WOM) among Emina Skincare users in Indonesia. Methodology: A quantitative survey approach was employed, collecting data through structured questionnaires from 150 respondents. Structural Equation Modeling (SEM) with WarpPLS 7.0 was used to analyze the relationships between variables. Results: The findings reveal that brand image and self-congruence significantly influence brand love, which enhances brand sacredness and WOM. Findings: The study highlights the importance of emotional drivers like brand love in fostering brand sacredness and encouraging positive WOM. Originality: This research contributes uniquely to understanding emotional attachment and brand advocacy in the local cosmetics market in Indonesia. Novelty: It addresses the gap in studying emotional branding and consumer behavior in emerging markets. Conclusions: Emina and similar brands should align their brand image with consumer identities, enhance emotional connections, and foster brand sacredness to encourage loyalty and positive WOM. Type of Paper: Survey-based quantitative research paper.